An introduction to biomaterials - Guelcher, Scott A. (Taylor & Francis, 2006)
The complexity of biological systems and the need to design and develop biomedical therapies poses major challenges to professionals in the biomedical disciplines. An Introduction to Biomaterials emphasizes applications of biomaterials for patient care. Containing chapters prepared by leading authorities on key biomaterial types, this book underscores the process of biomaterial design, development directed toward clinical application, and testing that leads to therapies for clinical targets. The authors provide a lucid perspective on the standards available and the logic behind the standards in which biomaterials address clinical needs. This volume includes chapters on consensus standards and regulatory approaches to testing paradigms, followed by an analysis of specific classes of biomaterials. The book closes with sections on clinical topics that integrate materials sciences and patient applications.